2020
DOI: 10.1007/s40090-020-00223-z
|View full text |Cite
|
Sign up to set email alerts
|

MgFe2O4/CNTs nanocomposite: synthesis, characterization, and photocatalytic activity

Abstract: Magnesium ferrite is a visible light absorber, and when combined with multiwall carbon nanotubes (MWCNTs), it can lead to low electron-hole recombination rates, thus improving its photocatalytic activity. In this work, a novel MgFe 2 O 4 /CNTs nanocomposite catalyst has been synthesized via anchoring MgFe 2 O 4 nanoparticles onto MWCNTs surface by a sol-gel and microwave-assisted route. The prepared catalyst was characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, scanning and transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…It is well reported that • O2 − and • OH radicals are the reactive species responsible for the initiating photooxidative degradation reaction of MB in the catalytic system [1,25,75]. Based on that, a possible mechanism (Fig.…”
Section: Mechanism Of Mb Photodegradation Over Mfo-cuo/go Nanocatalystmentioning
confidence: 93%
See 2 more Smart Citations
“…It is well reported that • O2 − and • OH radicals are the reactive species responsible for the initiating photooxidative degradation reaction of MB in the catalytic system [1,25,75]. Based on that, a possible mechanism (Fig.…”
Section: Mechanism Of Mb Photodegradation Over Mfo-cuo/go Nanocatalystmentioning
confidence: 93%
“…Nano-crystalline magnesium ferrite (MgFe2O4) was synthesized via an auto combustion technique, following a procedure described in our previous work [25].…”
Section: Synthesis Of Mgfe 2 O 4 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct activity is due to colouring of water and changing its composition, which significantly deteriorates the living conditions, but indirect activity is due to poisonous properties of many dyes. In this respect, adsorption has gained an important credibility during recent years because of its good performance and low cost, 3 much selective, easy to operate and a proven efficient process for the removal of dyes from contaminated aqueous media. 4 Actually, conjugated polymers, particularly those based on polyaniline (PANI), polythiophene (PT) and their derivatives, have gained interesting popularity because of multiple properties such as the low cost synthesis and their numerous applications in rechargeable batteries, display devices and sensors, porous structure, tunable morphology, good electrorheological property, unique redox chemistry, non-toxicity, insolubility in water, environmental stability.…”
Section: Introductionmentioning
confidence: 99%
“…Direct activity is due to colouring of water and changing its composition, which significantly deteriorates the living conditions, but indirect activity is due to poisonous properties of many dyes. In this respect, adsorption has gained an important credibility during recent years because of its good performance and low cost, 3 much selective, easy to operate and a proven efficient process for the removal of dyes from contaminated aqueous media. 4…”
Section: Introductionmentioning
confidence: 99%